ANALISIS BEBAN KERJA DAN KEBUTUHAN TENAGA PERAWAT DI PUSKESMAS PONCOL KOTA SEMARANG - RIZCARACHMAKURNIA, NAFIZTA; Wigati, Putri Asmita; Sriatmi, Ayun (Fakultas Kesehatan Masyarakat Universitas Diponegoro, 2017)
Human Resources Health is one component that needs to be considered in the implementation of health services in Puskesmas. PuskesmasPoncol only has three nurses so there is a gap if based on the standard of the Minister of Health Regulation number 75 of 2014. PuskesmasPoncol has many development programs, puskesmas auxiliaries, and experienced a significant increase in the number of visits in the era of JKN. Therefore, it is necessary to analyze the workload and the need of nurse personnel at the Poncol Community Health Center. This research was conducted using qualitative research method by using observational work sampling technique and then for the calculation of the need of nurse employed by Health Workload Analysis method.Based on the result of the research, it is known that productive time used by nurses is 84,52% and non productive time is 15,48%. The percentage has exceeded the standard productive time of 75% so it is concluded that nurses have high work productivity. The workload of nurse personnel is highest on Monday and Thursday, because patients who come more crowded, there are schedules puskesmas auxiliary, and often use overtime. It describes that the current work productivity is too high and affects the workload of nurses. The ideal nurse requirement is 4 people. The results of this study suggest that PuseksmasPoncol can minimize the division of tasks that are not nurse area. In addition, nurses can maximize communication and coordination with other health personnel in the completion of tasks.